Undersea warriors the untold history of the Royal Navy's secret service - Ballantyne, Iain, 1963 (Pegasus Books, 2019)
The dramatic untold story of Britain's most-silent service and of the Cold War beneath the waves--especially the frozen north--particularly British attack and nuclear submarines spying on the Soviets